Rumor retransmission on Twitter : message characteristics, user characteristics and retransmission outcomes - Chua, Alton Yeow Kuan (2020)
This paper seeks to depict online rumor retransmission using three main constructs, namely, message characteristics, user characteristics and retransmission outcomes. In particular, it teases retransmission outcomes into volume, immediacy and lifespan of rumor tweets. The dataset was drawn from 322 original Twitter messages which generated some 5,700 retweets about the rumored death of Lee Kuan Yew (LKY). Content analysis and statistical tests were conducted. The results confirm the robustness of the research model. Specifically, rumor message characteristics affect retransmission in terms of volume, immediacy and lifespan. Additionally, user characteristics are positively related to volume and immediacy. Finally, user characteristics have a moderating effect on the relationships between rumor message characteristics and retransmission outcomes. This paper illustrates the applicability of the information diffusion model on online rumor retransmission which hitherto has yet to be attempted. Moreover, it granularizes the concept of online rumor retransmission into three important outcomes, namely, volume, immediacy and lifespan. On the practical front, this paper has implications for organizations seeking to combat rumors.